2018
DOI: 10.1016/j.aninu.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fatty acid profile of three adipose tissues in Ningxiang pigs

Abstract: The present study is conducted to determinate fatty acids (FA) composition in 3 adipose tissues. Subcutaneous and perirenal adipose tissues were prepared from 24 Ningxiang castrated boars and 24 castrated gilts fattened by a traditional diet for 56 d, respectively. The results showed that the FA profile in the 3 adipose tissues (dorsal subcutaneous adipose [DSA], abdominal subcutaneous adipose [ASA], and perirenal adipose [PA]) differed greatly. In boars, the proportions of oleic acid (c18:1n9c) (P < 0.05), ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…Indeed, lipid synthesis mainly occurs in adipose tissues of pigs. Subcutaneous and visceral adipose tissues with different anatomical locations show specific development and deposition, especially in de novo synthesized fatty acids due to desaturation and elongation [43,44]. NCG is involved in regulating the metabolism of energy substrates through nitric oxide production [19,45].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lipid synthesis mainly occurs in adipose tissues of pigs. Subcutaneous and visceral adipose tissues with different anatomical locations show specific development and deposition, especially in de novo synthesized fatty acids due to desaturation and elongation [43,44]. NCG is involved in regulating the metabolism of energy substrates through nitric oxide production [19,45].…”
Section: Discussionmentioning
confidence: 99%
“…En la carne, el contenido de ácidos grasos saturados y monoinsaturados fue mayor, y el de poliinsaturados menor que en la grasa de cobertura (P ≤ 0,05). Esto se podría deber al consumo de forrajes verdes desde los inicios de su desarrollo, ya que la grasa subcutánea presenta una tasa de renovación más lenta que la grasa intramuscular (Jiang et al, 2018). En este estudio los animales estuvieron estabulados sin acceso a pradera el último mes, lo cual podría haber influido en la composición final de la grasa infiltrada en la carne.…”
Section: Resultados Y Discusiónunclassified
“…En este estudio los animales estuvieron estabulados sin acceso a pradera el último mes, lo cual podría haber influido en la composición final de la grasa infiltrada en la carne. Por lo tanto, para aumentar los ácidos grasos monoinsaturados y poliinsaturados en la carne de cerdos de sistema natural, sería recomendable prolongar el pastoreo hasta el final del proceso productivo (Jiang et al, 2018). Álvarez-Rodríguez et al (2016) determinaron un mayor contenido de ácidos grasos poliinsaturados en carne de cerdos de sistema orgánico, pero sin acceso a praderas, comparado con cerdos de sistema convencional, lo que se atribuye a ácidos grasos contenidos en la soya, como el α-linolénico (18:3n3).…”
Section: Resultados Y Discusiónunclassified
“…Ningxiang pigs are well-known for their excellent meat quality and have become one of the four best-known local breeds in China. It has been reported that unsaturated fatty acids (UFAs) in Ningxiang pork account for up to 59.6% of all fatty acids [2].Moreover, He etal. [3] found that the serum of Ningxiang pigs contains more unsaturated lipids than that of lean pigs under the same environment and feeding conditions.…”
Section: Introductionmentioning
confidence: 99%